1989
DOI: 10.1097/00000658-198905000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bacteria in Gallbladder and Common Duct Stone Formation

Abstract: Debate continues as to the role that bacteria play in gallstone pathogenesis in Western countries. We therefore, examined gallbladder and common duct stones from 67 consecutive patients undergoing cholecystectomy and/or common bile duct exploration. Bile was cultured and stone cholesterol content was measured. Stones were examined by scanning electron microscopy (SEM) for bacteria. Individual calcium salts were classified by windowless energy-dispersive x-ray microanalysis. Gallbladder stones in 65 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
2
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(62 citation statements)
references
References 28 publications
1
57
2
2
Order By: Relevance
“…Pigment stones were associated with positive bacterial culture, as observed in other studies [3,10,13], Because stones from the bile duct are mainly of the pigment type, bile duct stones are also associated with positive bacterial culture. It has been reported [3,12,13] that bacterial infection and bacterial (J-glucuronidase may play a key role in the pathogenesis of pigment stones.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Pigment stones were associated with positive bacterial culture, as observed in other studies [3,10,13], Because stones from the bile duct are mainly of the pigment type, bile duct stones are also associated with positive bacterial culture. It has been reported [3,12,13] that bacterial infection and bacterial (J-glucuronidase may play a key role in the pathogenesis of pigment stones.…”
Section: Discussionsupporting
confidence: 78%
“…Positive bacterial culture, which reflects biliary bacte rial infection, is reportedly observed in 20-40% of the patients with gallstones [10,11]. However, in our study this percentage was higher (57%).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The real incidence of primary CBD stone is controversial and varies widely from 4% to 56%, according to the different methods of identification or definition [4] [5]. Biliary infection and biliary stasis have been implicated as important factors in formation of primary duct stones [6].…”
Section: Introductionmentioning
confidence: 99%
“…In a SEM (scan-ning electron microscopy) study, bacteria were observed only within the calcium bilirubinate-protein matrix of brown pigment stones (P < 0.001). In comparison to black pigment stones, brown stones were more likely to contain calcium palmitate (P < 0.005) and cholesterol (P < 0.001) (19). Bacterial properties determine the path of gallstone formation, for instance, β-glucuronidase and urease activity are involved in calcium precipitation in cholesterol and pigmented stones, respectively.…”
Section: Introductionmentioning
confidence: 99%